(untitled) (Filološke studije, 2019)
The paper deals with group interjections which are used in the metalinguistic function in texts for children. The research is based on literary texts of the Macedonian language to select interjections and onomatopoeia and to make the Macedonian interjections and onomatopoeia dictionary.